1995
DOI: 10.1302/0301-620x.77b6.7593095
|View full text |Cite
|
Sign up to set email alerts
|

Early migration of femoral components revised with impacted cancellous allografts and cement. A preliminary report of five patients

Abstract: We report the preliminary findings of the use of roentgen stereophotogrammetric analysis to evaluate the early migration of five femoral components after revision for mechanical loosening using impacted cancellous allograft and cement. All hips were examined at one week, four to six months and one year after surgery. All the components subsided by 0.4 to 4.9 mm during the first year. In four hips the prosthetic head was displaced 1.1 to 6.9 mm posteriorly. Fixation of the femoral components was less secure tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 0 publications
4
23
0
3
Order By: Relevance
“…The allografts appear stable enough to withstand the forces of walking with the newly-inserted prosthesis. Although migrating more than primary arthroplasties (Franzen et al 1995, Sandquist et al 1996, follow-up series have shown excellent clinical results for up to 9 years (Ling 1996, Slooff et al 1996. Radiographically, the grafts seem to remodel and within the first year a neocortex is often visible.…”
Section: Discussionmentioning
confidence: 99%
“…The allografts appear stable enough to withstand the forces of walking with the newly-inserted prosthesis. Although migrating more than primary arthroplasties (Franzen et al 1995, Sandquist et al 1996, follow-up series have shown excellent clinical results for up to 9 years (Ling 1996, Slooff et al 1996. Radiographically, the grafts seem to remodel and within the first year a neocortex is often visible.…”
Section: Discussionmentioning
confidence: 99%
“…Cemented prostheses, surrounded by an envelope of impacted morsellized bone, are widely used in revision hip surgery (Gie et al 1993, Welten et al 2000, Schreurs et al 2003. Early axial subsidence and torsion may disturb the geometry of the implant system and hence reduce the durability of the revised prosthesis (Franzén et al 1995, Eldridge et al 1997, Brodt et al 1998, Ornstein et al 2002. Various factors influence the mechanical stability of impacted bone: particle size and grading (Brewster et al 1999, Ullmark 2000, moisture (Voor et al 2000, Dunlop et al 2003, addition of bone substitutes (Verdonschot et al 2001), and impaction energy (Ullmark 2000, Fosse et al 2004.…”
mentioning
confidence: 99%
“…Radiosterometric measurements are the most accurate way to measure subsidence [9]. Polished stems are supposed to subside into the cement mantle during the initial phases without clinical relevance (cold flow phenomenon) [14].…”
Section: Discussionmentioning
confidence: 99%